Maternal theory : essential readings - O'Reilly, Andrea, 1961- (Demeter Press, 2007)
Theory on mothers, mothering and motherhood has emerged as a distinct body of knowledge within Motherhood Studies and Feminist Theory more generally. This collection, the first ever anthology on maternal theory, introduces readers to this rich and diverse tradition of maternal theory. Composed of 50 chapters and covering more than three decades of scholarship, Maternal Theory includes all the must read theorists on motherhood. Writers include: Adrienne Rich, Nancy Chodorow, Sara Ruddick, Alice Walker, Barbara Katz Rothman, bell hooks, Sharon Hays, Patricia Hill-Collins, Julia Kristeva, Kim Anderson, Audre Lorde, Ellen Lewin, Daphne de Marneffe, Ariel Gore, Ann Crittenden, Judith Warner and many more. Maternal Theory is essential reading for anyone interested in motherhood as experience, ideology, and identity.